Pengukuran Efisiensi Serta Analisis Faktor Internal dan Eksternal Bank yang Memengaruhinya (Jurnal Manajemen dan Organisasi, 2020)
Efficiency for the banking industry as a whole is the most important aspect considered to realize healthy and sustainable financial performance. Therefore, to realize a healthy and sustainable financial performance, the government intervenes in the banking business to divide or categorize banks based on core capital. This study will measure the efficiency level of conventional commercial banks with input variables that are thought to affect the output variable using non-parametric methods with the Data Envelopment Analysis (DEA) model. Bank size (SIZE), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) proved to have a significant positive effect on the efficiency of banks listed on the Indonesia Stock Exchange for the period 2013-2017. Meanwhile, non-performing loan (NPL) proved to have a significant negative effect on the efficiency of banks listed on the Indonesia Stock Exchange for the period 2013-2017. External factors such as the rupiah exchange rate (KURS), Bank Indonesia interest rates (SBI), and gross domestic product (GDP) have proven to have no significant positive effect on the efficiency of banks listed on the Indonesian Stock Exchange in the period 2013-2017.